Respiratory syncytial virus fuses with plasma membrane to infect primary cultures of bronchial epithelial cells - Christian Cadena-Cruz; Christian Cadena-Cruz; Marcio De-Avila-Arias; Heather M. Costello; Leidy Hurtado-Gomez; Walter Martínez-De-La-Rosa; Gigliola Macchia-Ceballos; Wendy Rosales-Rada; Wendy Rosales-Rada; Gerardo Valencia-Villa; Pedro Villalba-Amarís; Meisam Naeimi Kararoudi; et al. (Frontiers in Microbiology)
BackgroundRespiratory syncytial virus (RSV) is a common cause of bronchiolitis in children under the age of five. RSV infection proceeds by fusion of the viral envelope with the target cell membrane, but it is unclear whether fusion occurs with plasma or endosomal membranes.MethodsEntry and/or infection was studied in undifferentiated primary cultures of human bronchial epithelial cells. Synchronization of viral entry or infection was achieved by attaching the virus to the plasma membrane at temperatures of 4°C or 22°C. Cells in which entry events had occurred were identified by the enzymatic action of beta-lactamase M (BlaM) fused to the RSV P protein (BlaM-P) carried by rgRSV virions. BlaM cleaves the beta-lactam ring of CCF2 loaded into the cells, disrupting FRET and allowing blue light to be emitted. Green fluorescent protein (GFP) expression, encoded by the rgRSV genome, was used to identify infected cells.ResultsWe found that adsorption of RSV at 4°C favors entry via endocytosis, whereas binding of the virus to the membrane at 22°C favors RSV entry via the plasma membrane. The induction of endocytosis by synchronization at 4°C is, therefore, an artifact. In addition, we found that all drugs that interfered with RSV infection reduced cell membrane deformations such as filopodia and lamellipodia, suggesting a mechanism by which they may interfere with RSV fusion with the cell membrane.DiscussionIn conclusion, RSV enters the cell by direct fusion of its envelope with the plasma membrane.